Teologiczny profil znaków czasu - Moskałyk, Jarosław (Poznańskie Studia Teologiczne, 2022)
The signs of the times, as particular phenomena in human history, demand above all to be recognized in relation to revelation. Because this the Bible that creates the true background for their theological understanding and at the same time for their salvific character. The human interpretation of the meaning of a sign, including in terms of religious content, is characterized by a rather diverse perspective. Generally speaking, it can be reduced to positive and negative, but it undoubtedly contributes to the experience and development of a person. However, in a theological sense, the signs of the times leave a lasting feeling of both inaccessibility and cognitive inexhaustibility.